Evaluation of a federally funded mass media campaign and smoking cessation in pregnant women: a population-based study in three states. Issue 12 (19th December 2017) - England, Lucinda; Tong, Van T; Rockhill, Karilynn; Hsia, Jason; McAfee, Tim; Patel, Deesha; Rupp, Katelin; Conrey, Elizabeth J; Valdivieso, Claudia; Davis, Kevin C
Abstract : Objectives: In 2012, theCenters for Disease Control and Prevention initiated a national anti-smoking campaign, Tips from Former Smokers ( Tips ). As a result of the campaign, quit attempts among smokers increased in the general population by 3.7 percentage points. In the current study, we assessed the effects of Tips on smoking cessation in pregnant women. Methods: We used 2009–2013 certificates of live births in three US states: Indiana, Kentucky and Ohio. Smoking cessation by the third trimester of pregnancy was examined among women who smoked in the 3 months prepregnancy. Campaign exposure was defined as overlap between the airing of Tips 2012 (March 19–June 10) and the prepregnancy and pregnancy periods. Women who delivered before Tips 2012 were not exposed. Adjusted logistic regression was used to determine whether exposure to Tips was independently associated with smoking cessation. Results: Cessation rates were stable during 2009–2011 but increased at the time Tips 2012 aired and remained elevated. Overall, 32.9% of unexposed and 34.7% of exposed smokers quit by the third trimester (p<0.001). Exposure to Tips 2012 was associated with increased cessation (adjusted OR: 1.07, 95% CI 1.05 to 1.10). Conclusions: Exposure to a national anti-smoking campaign for a general audience was associated with smoking cessation in pregnant women.